Prospek Penggunaan Mikroba Antagonis sebagai agens pengendali hayati penyakit utama pada tanaman hias dan sayuran - Hanudin .; Budi Marwoto (Jurnal Penelitian dan Pengembangan Pertanian, 2012)
Cultivation of ornamental plants and vegetables faces various problems that inhibit efforts to increase plant production. One of the most important constraints is disease incidences, i.e. wilt disease (Fusarium spp.) on carnation, damping off (Rhizoctonia spp.) on chrysanthemum, bacterial wilt (Ralstonia solanacearum) on Solanaceae, and club root (Plasmodiophora brassicae) on Barssicaceae. One of environmentally-friendly control methods is application of antagonistic microorganisms. The purpose of this paper is to inform prospects of the use of microbial antagonists as biological control agents of major diseases on ornamental plants and vegetables. Antagonistic microbes are the bacteria, fungi, actinomycetes or virus that can suppress other microbes. Antagonistic bacteria (Bacillus subtilis and Pseudomonas fluorescens), antagonistic fungi (Trichoderma harzianum, Gliocladium sp., and non-pathogenic Fusarium), actinomycetes (Streptomyces spp.), and virus (Carna-5 vaccine) are known to be effective as biological control agents. Their use as a biological control agent is proven to be  prospective since their isolation techniques, propagation and biopesticide formulation are well known by inventors in Indonesia. Nowdays, the microbes have been formulated by various research institutes as microbial pesticides and licenced to private company and commercialized widely to the domestic market. This indicates that prospect of application of antagonistic microbe is very bright to control major diseases of ornamental plants and vegetables.